A better way to detect head and neck cancer recurrences. Issue 1 (January 2022) - Abbas, Aya; Prabhu, Satheesh; Shah, Rahul
Abstract : Introduction: To examine the prevalence of recurrence following multidisciplinary, multimodality curative head and neck cancer (H&NC) treatment, to determine how, when and where recurrences are identified and, most pertinently, who was identifying them; patients, clinicians or routine imaging. Methods: We reviewed all H&NC cases that presented to the Blenheim Head and Neck unit over 2.5 years and were discussed in MDT, and isolated those which represented recurrences at clinically detectable anatomical regions. We explored the types of cancers most commonly recurring, the primary sites and the initial treatment they were provided. We examined the frequency and mode of surveillance they underwent and we explored how these clinically identifiable recurrences were being discovered. Results: 1108 cases of head and neck cancer were discussed in MDT over this period. Of these 736 met the inclusion criteria. 11% of these represented confirmed recurrent disease. 91% of cases were biopsied as SCCs. The most common primary sites were the tongue (33%) and tonsils (11%). 67% of recurrences presented with symptoms identified by the patients. Of those, 61% were seen in clinic, most commonly during an expedited routine follow-up appointment, and 31% attended their GP. Imaging and clinicians picked up most of the remainder. We found no significant reduction in the pick-up rate related to COVID-19. Conclusions: Studies have found no surveillance protocol post H&NC fits all, and follow-up should be considered on a case-by-case basis. Here we show that patients play a crucial role in the identification of recurrence, and increased education and regular open access clinics for follow-up with the MDT may be a safe and cost-effective approach.